Intense immunostaining of heat shock protein 70 within renal interstitium associates with long-term renal survival in an ANCA-associated vasculitis cohort - Petrakis, Ioannis; Androvitsanea, Ariadni; Stratakis, Stavros; Daphnis, Eugene; Stylianou, Kostas (Cell Stress & Chaperones, 2020)
In anti-neutrophilic cytoplasmic antibody (ANCA)-associated vasculitis (AAV) genetic predisposition, ANCA autoantibodies, neutrophil extracellular traps (NETs), complement activation, and toll-like receptor signaling are implicated in AAV pathogenesis. Heat shock proteins (HSPs), a highly conserved group of small-sized molecular chaperones, take part in protein folding during cellular stress. Although HSPs were initially observed intracellularly, it has been shown that they can be secreted in the extracellular space and modulate the immune response in various autoimmune diseases including AAV. The scope of the present study is to investigate the role of heat shock protein 60 (HSP60) and 70 (HSP70) in the long renal effects in an ANCA vasculitis cohort. In this cohort of ANCA-associated vasculitis, 29 patients were followed up over 20 years. At diagnosis, immunohistochemistry was performed for HSP60 and HSP70 within the various nephron compartments. Higher renal HSP60 expression was associated with increased interstitial inflammatory infiltrates at diagnosis, while HSP70 expression was associated with a greater extent of interstitial fibrosis at diagnosis. Notably, intense tissue expression of HSP70 at the time of biopsy was associated with a worsened kidney survival. Renal HSP70 expression was associated with poor renal outcomes during long-term follow-up. This finding may indicate a role of HSPs in renal disease progression in ANCA vasculitis. Further validating studies are needed to verify a causative association between HSP70 expression and renal outcomes in ANCA-associated vasculitis.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ANCA-vasculitis; Heat shock protein; Interstitial fibrosis; Interstitial inflammation; Pauci-immune glomerulonephritis